Affinity proteomics within rare diseases: a BIO‐NMD study for blood biomarkers of muscular dystrophies - Burcu Ayoglu; Amina Chaouch; Hanns Lochmüller; Luisa Politano; Enrico Bertini; Pietro Spitali; Monika Hiller; Eric H Niks; Francesca Gualandi; Fredrik Pontén; Kate Bushby; Annemieke Aartsma‐Rus; et al. (EMBO Molecular Medicine, 2014)
Abstract Despite the recent progress in the broad‐scaled analysis of proteins in body fluids, there is still a lack in protein profiling approaches for biomarkers of rare diseases. Scarcity of samples is the main obstacle hindering attempts to apply discovery driven protein profiling in rare diseases. We addressed this challenge by combining samples collected within the BIO‐NMD consortium from four geographically dispersed clinical sites to identify protein markers associated with muscular dystrophy using an antibody bead array platform with 384 antibodies. Based on concordance in statistical significance and confirmatory results obtained from analysis of both serum and plasma, we identified eleven proteins associated with muscular dystrophy, among which four proteins were elevated in blood from muscular dystrophy patients: carbonic anhydrase III (CA3) and myosin light chain 3 (MYL3), both specifically expressed in slow‐twitch muscle fibers and mitochondrial malate dehydrogenase 2 (MDH2) and electron transfer flavoprotein A (ETFA). Using age‐matched sub‐cohorts, 9 protein profiles correlating with disease progression and severity were identified, which hold promise for the development of new clinical tools for management of dystrophinopathies.